INFORMATION LITERACY IN EARLY CHILDHOOD EDUCATION - Fatia FATIMAH; Yusrafiddin YUSRAFIDDIN; Muhammadi MUHAMMADI; Refny DELFI; dasrul DASRUL; harnon HARNON; Zaimal GUSTI (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2019)
Literacy could be a supporter of the forefront of education. Teachers have a crucial role in filtering and remodeling data on their students. The utilization of knowledge skill has to be trained by sorting and selecting the proper media for learning whose main purpose is to extend students' intelligence. Skill coaching is a way to boost the flexibility to use learning media, particularly Early Childhood Education and Kindergartens in Lubuk Begalung, Padang. The objectives to be achieved include: to increase the insight of Early Childhood Education and Kindergarten teachers about media, and the ability of media information literacy in learning. Training methods i.e. lectures, discussions, questions, and answers, and case simulations. The conclusion obtained from this activity is that early childhood and kindergarten teachers can choose the media responsibly and able to criticize media content more intelligent in the classroom.